1987
DOI: 10.1037/0097-7403.13.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Time horizons in rats foraging for food in temporally separated patches.

Abstract: An important tenet of optimal foraging theory is that foragers compare prey densities in alternative patches to determine an optimal distribution of foraging behavior over time. A critical question is over what time period (time horizon) this integration of information and behavior occurs. Recent research has indicated that rats do not compare food density in a depleting patch with that in a rich patch delayed by an hour or more (Timberlake, 1984). In the present research we attempted to specify over what time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 36 publications
6
66
0
2
Order By: Relevance
“…If contrast occurred when time-outs were 16 min long, but not when they were 32 min long, then the results would be consistent with Timberlake's findings (e.g., Lucas et al, 1988;Timberlake et al, 1987). This would show that the time course for integrating rewards hassome generality across species (pigeons as weil as rats), procedures (behavioral contrast as well as anticipatory contrast or foraging), and the absence of rewards as weIl as their presence.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…If contrast occurred when time-outs were 16 min long, but not when they were 32 min long, then the results would be consistent with Timberlake's findings (e.g., Lucas et al, 1988;Timberlake et al, 1987). This would show that the time course for integrating rewards hassome generality across species (pigeons as weil as rats), procedures (behavioral contrast as well as anticipatory contrast or foraging), and the absence of rewards as weIl as their presence.…”
Section: Discussionsupporting
confidence: 78%
“…Timberlake has also shown that animals may integrate rewards over intervals as long as 16 min (e.g., Lucas, Gawley, & Timberlake, 1988;Timberlake, Gawley, & Lucas, 1987). In a procedure sirnilar to that used to study behavioral contrast, Lucas et al (1988) measured the consumption of a 0.15 % saccharin solution followed by a 32 % sucrose solution.…”
mentioning
confidence: 99%
“…Timberlake (1984) found that responding at high ratios in progressiveratio schedules was not reduced by free food given an hour after the session. Timberlake, Gawley, and Lucas (1987) extended these results, showing that only when free food was available within 15 min of the end of the session was responding affected. The findings of Timberlake and associates rule out any important substitution effect due to supplemental feeding.…”
mentioning
confidence: 48%
“…However, the psychological literature reveals that anticipation of future events based on earlier exposure is unlikely to alter current behavior unless future events occur within minutes. Rats, for instance, will work hard to obtain vanishing resources despite the fact that all their food could be obtained from a rich patch that materializes only 15 min later (Timberlake et al 1987). That is, they were unaffected by the availability of future foraging opportunities beyond a time horizon of 15 min.…”
Section: Cognitive Constraintsmentioning
confidence: 99%